Synthesis and characterization of pan nanofiber reinforced with functionalized mixture CNT/CNF by electrospinning technique - Bryan Gindana (2016)
In this study, functionalization of CNT and CNF was done using oxidative acid treatment with concentrated HCl and HN03 solution mixture at 3: 1 ratio. Various process variables such as duration, mode of treatment, agitation and temperature are controlled, and consequently the functional groups growth on the surfaces of both CNT and CNF was determined extensively by the aid of Fourier Transform Infrared Spectroscopy (FTIR). The study proceeds by synthesizing the PAN/CNTCNF polymer nanocomposite fiber using electrospinning technique. The study used PAN polymer solution containing 10 wt % mixture of CNT: CNF at various ratios of 8: 2,2: 8,6: 4, and 4: 6. Some critical criterions of operational parameters such as applied voltage (12 kV, 12.5 kV, 13 kV) and working distance (13 cm, 14 cm, 15 cm) were also being optimized beforehand. The available evidences supported that, the optimal operational parameter set was found to be at 15 cm, 13 kV set division as validated by series of scrutinized characterization assessments; where the set up successfully produced the thinnest average nanofiber diameter at 318 nm with the range of 288 to 340 nm. The graphitized nanocomposite fiber was then assessed and characterized comprehensively based on its morphological and elementary study using FESEM-EDX, thermal stability behaviour using TGA and DSC, crystallography assessment by XRD analysis, and conductivity study via EIS. Based on the overall assessment of various field of characterizations, overwhelming evidences has led to the confirmatory conclusion, corroborating PB15Z as the best electrospun PAN/CNT-CNF nanocomposite fiber with an exceptionally thin fiber diameter of 280 nm with 232 nm to 304 nm in range. It possessing the highest carbon content approximately 80 % in total and a good conductivity value recorded at 2.3555 x 10-4 S/m. The fiber also showed the most stable behaviour under intense heat exposure, withstanding the thermal introduction with gradual decrease of weight without any sudden and major fluctuation of weight.